STOCK PRICE AND PROFITABILITY IMPROVEMENT OF PT HATTEN BALI TBK - Drestanto R. D., Hanif
The COVID-19 pandemic has hit the tourism industry and the creative economy in Indonesia. Covid 19 has had a major impact on the arrival of international tourists visiting Indonesia. This decrease is because the Indonesian border has been closed to international tourists. A city that is heavily dependent on international tourists is very toxic about this. The decline had a direct impact on hotel occupancy, reduced revenue at restaurants and bars. In addition to the tourism sector which was affected, many industrial sectors in a country were also affected, one of which was the food and beverage industry. Bali is known for its natural wealth and stunning panoramas. It is not surprising that various regions in the archipelago are destinations frequently visited by tourists, both local and foreign. And one that has been affected by the beverage industry, namely wine, currently the demand for wine-type drinks is growing and has become a trend because it is liked by Indonesian people, from local tourists to foreign tourists. The need for wine in Bali is supplied not only from importers and many local players, one of which is that Hatten Wine is still able to achieve a large turnover in one month during normal conditions. However, in the midst of the Covid-19 pandemic, wine sales have decreased by 90%. However, currently the Indonesian government has revoked the status related to social reform in December 2020. This is accepted by both local and international tourists to return to traveling in Indonesia comfortably and easily. Hatten Bali itself has currently conducted an IPO with the WINE code on January 10, 2023. The composition of the company's capital structure is 51.02% debt and 48.98% equity with a cost of debt after tax of 7.68%. The company's final WACC yield is 10.48%. The results of calculating the company's stock price based on absolute valuation using discounted cash flow before improvement is Rp. 310 (downside) while after the repair is Rp. 945, with today's share price of Rp. 545. From these findings it can be interpreted that the company is currently undervalued and uses a relative assessment of overvalued company value ratios in terms of EV/Revenue, EV/EBITDA, and PE ratios. Then after increasing profitability it was found that EV/Revenue, EV/EBITDA, and PER increased and were better than similar companies at this time.